Evaluation of operational on-line-coupled regional air quality models over Europe and North America in the context of AQMEII phase 2. Part I: Ozone. (August 2015) - Im, Ulas; Bianconi, Roberto; Solazzo, Efisio; Kioutsioukis, Ioannis; Badia, Alba; Balzarini, Alessandra; Baró, Rocío; Bellasio, Roberto; Brunner, Dominik; Chemel, Charles; Curci, Gabriele; Flemming, Johannes; et al.
Abstract: The second phase of the Air Quality Model Evaluation International Initiative (AQMEII) brought together sixteen modeling groups from Europe and North America, running eight operational online-coupled air quality models over Europe and North America on common emissions and boundary conditions. With the advent of online-coupled models providing new capability to quantify the effects of feedback processes, the main aim of this study is to compare the response of coupled air quality models to simulate levels of O3 over the two continental regions. The simulated annual, seasonal, continental and sub-regional ozone surface concentrations and vertical profiles for the year 2010 have been evaluated against a large observational database from different measurement networks operating in Europe and North America. Results show a general model underestimation of the annual surface ozone levels over both continents reaching up to 18% over Europe and 22% over North America. The observed temporal variations are successfully reproduced with correlation coefficients larger than 0.8. Results clearly show that the simulated levels highly depend on the meteorological and chemical configurations used in the models, even within the same modeling system. The seasonal and sub-regional analyses show the models' tendency to overestimate surface ozone in all regions during autumn and underestimate in winter. Boundary conditions strongly influence ozone predictions especially during winter and autumn, whereas during summer local production dominates over regional transport. Daily maximum 8-h averaged surface ozone levels below 50–60 μg m −3 are overestimated by all models over both continents while levels over 120–140 μg m −3 are underestimated, suggesting that models have a tendency to severely under-predict high O3 values that are of concern for air quality forecast and control policy applications. Highlights: Sixteen modeling groups from EU and NA simulated O3 for 2010 under AQMEII phase 2. A general model underestimation of surface O3 over both continents up to 22%. Models tend to over/under estimate surface O3 in all regions during autumn/winter. Boundary conditions influence O3 predictions especially during winter and autumn. Models tend to under-predict high O3 values that are of concern for policy.